Study of prescribing pattern of drugs used in the treatment of hypertension in a tertiary care teaching hospital in North India: an observational study - Gupta, Rohini; Malhotra, Apoorva; Malhotra, Pavan (International Journal of Research in Medical Sciences, 2018)
Background: Hypertension is one of the most common chronic diseases leading to high mortality and morbidity. In order to prevent complications and to improve the patient survival, the early and efficient management of essential hypertension is very much needed. In this context, the use of established anti-hypertensives assumes paramount importance. Objective was to study the prescribing pattern of anti-hypertensive drugs in a tertiary care teaching hospital in north India. Methods: It was a cross-sectional observational study involving 205 prescriptions for patients suffering from primary essential hypertension in the Medicine Outpatient Department of Acharaya Shri Chander College of Medical Sciences and Hospital, Sidhra, Jammu, J and K. All hypertensive patients irrespective of age and sex visiting OPD and treated with at least one hypertensive drugs were included in the study. Data was obtained from the patients by scrutinizing the out patients regarding the demographic profile and details pertaining to the prescribing pattern of antihypertensive drugs used for the treatment of hypertension. Results: A total of 205 prescriptions were analysed during the study period. Out of which 131 (63.9%) were males and 74 (36.1%) were females. Maximum numbers of patients were in the age group of 50-59 years 60 (29.3%) patients. 145 (70.7%) of the patients had a family history of hypertension, (61.5%) of the patients were in stage-I hypertension and (56.1%) were of normal BMI. The results revealed that, the maximum number of 86 (41.9%) patients underwent dual therapy in 86 (41.9%) followed by monotherapy in 59 (28.7%) of patients. Conclusions: From the present study, it can be concluded that in hypertension calcium channel blockers are the most frequently prescribed classes of drugs alone and diuretics are the most commonly used class of drugs in combination. However, further studies are necessary to set up a rationale or pattern for the choice of medication; taking into consideration the demographic factors involved in the prevalence of hypertension.